EKPLORASI TARI KREASI MELALUI PROJECT BASED LEARNING SEBAGAI UPAYA PENINGKATAN KREATIVITAS DAN KOLABORASI PADA SISWA KELAS V SD - Wijiastuti, Arum; Rusnoto Susanto, Moh. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Project-based learning method integrates practical and creative approaches in learning, involving students in real projects that encourage them to collaborate and innovate. In learning, the importance of developing creativity and collaboration in the field of Creative Dance is crucial. Creativity and collaboration are key factors in the development of dance art, as they enable students to produce original works and merge their ideas with others. This research aims to explain the impact of implementing the project-based learning method in developing creativity and collaboration skills in the context of Creative Dance. This research method utilizes a descriptive method. The research was conducted with fifth-grade students at a primary school in Kebumen. The research instruments include attitude observation, skill assessment, product assessment, and data analysis using descriptive analysis. The results show that students are more active during the learning process and can enhance creativity and collaboration skills. The implementation of project-based learning method in Creative Dance can significantly benefit in improving students' creativity and collaboration skills. The implications of this research indicate the necessity of involving students in real projects that allow them to innovate and actively collaborate in the Creative Dance learning process.